2003
DOI: 10.1519/1533-4287(2003)017<0053:teoiod>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ibuprofen on Delayed Muscle Soreness and Muscular Performance After Eccentric Exercise

Abstract: The purpose of this study was to examine the effects of ibuprofen on delayed onset muscle soreness (DOMS), indirect markers of muscle damage and muscular performance. Nineteen subjects (their mean [+/- SD] age, height, and weight was 24.6 +/- 3.9 years, 176.2 +/- 11.1 cm, 77.3 +/- 18.7 kg) performed the eccentric leg curl exercise to induce muscle soreness in the hamstrings. Nine subjects took an ibuprofen pill of 400 mg every 8 hours within a period of 48 hours, whereas 10 subjects received a placebo randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 27 publications
1
66
0
Order By: Relevance
“…Also the effect of a prophylactic dose of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) on muscle damage or soreness is controversial. Tokmakidis et al (2003) reported that ibuprofen use compared to nonuse by athletes can decrease muscle soreness induced after eccentric exercise which is not comparable to the results of some other similar studies (Suzuki et al, 20002;Semark et al, 1999;Nieman et al, 2006). Since ibuprofen did not affect the inflammatory cytokines in untrained athletes, so the etiology of athletes muscle soreness seems to be independent of increases in prostaglandin (Semark et al, 1999).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Also the effect of a prophylactic dose of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) on muscle damage or soreness is controversial. Tokmakidis et al (2003) reported that ibuprofen use compared to nonuse by athletes can decrease muscle soreness induced after eccentric exercise which is not comparable to the results of some other similar studies (Suzuki et al, 20002;Semark et al, 1999;Nieman et al, 2006). Since ibuprofen did not affect the inflammatory cytokines in untrained athletes, so the etiology of athletes muscle soreness seems to be independent of increases in prostaglandin (Semark et al, 1999).…”
Section: Discussionmentioning
confidence: 86%
“…Semark et al (1999) reported that a prophylactic dose of flurbiprofen did not affect Delayed-Onset Muscle Soreness (DOMS), muscle soreness in trained subjects (Semark et al, 1999). However, Kokkinidis et al reported that ibuprofen decreased muscle soreness induced after eccentric exercise (Tokmakidis et al, 2003). However, Nieman et al (2006) reported that ibuprofen use compared to nonuse by athletes competing in a 160 km race did not alter muscle damage or soreness but decreased inflammatory cytokines (Nieman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Among these practices is the use of anti-inflammatories [1], supplementation with minerals and antioxidant vitamins [2], and higher intake of protein, carbohydrates, electrolytes, and fluids [3,4]. Anti-inflammatory medications can reduce the pain and edema that accompany training and may expedite training recovery and restoration of performance capacity [5][6][7][8]. Similarly, supplemental antioxidants carry the potential to enhance exercise performance by reducing the detrimental effects of reactive oxygen species [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between NSAI and strength training (also called resistance training) has already been approached by investigations which focused on the effects of the prophylactic 12,13 or therapeutic use 12,[14][15][16] of these pharmaceuticals in the treatment of the symptoms of muscular damage induced by eccentric exercise, especially delayed muscular pain. Moreover, the chronic effect of NSAI use on the hypertrophic response and the strength increase after a period of strength training has been studied 17,18 .…”
Section: Introductionmentioning
confidence: 99%